Chemosensory Sensitivity after Coffee Consumption Is Not Static: Short-Term Effects on Gustatory and Olfactory Sensitivity - Alexander W. Fjaeldstad; Henrique M. Fernandes (Foods, 2020)
Chemosensory sensitivity has great variation between individuals. This variation complicates the chemosensory diagnostics, as well as the creation of a meal with universally high hedonic value. To ensure accurate characterization of chemosensory function, a common rule of thumb is to avoid food/beverages one hour before chemosensory testing. However, the scientific foundation of this time of fast remains unclear. Furthermore, the role of coffee on immediate chemosensitivity is not known and may have implications for optimization of gastronomy and hedonia. The aim of this study is to investigate the modularity effects of coffee consumption on immediate gustatory and olfactory sensitivity. We included 155 participants. By applying tests for olfactory and gustatory sensitivity before and after coffee intake, we found no changes in olfactory sensitivity, but significantly altered sensitivity for some basic tastants. We repeated our experimental paradigm using decaffeinated coffee and found similar results. Our results demonstrate that coffee (regular and decaffeinated) alters the subsequent perception of taste, specifically by increasing the sensitivity to sweet and decreasing the sensitivity to bitter. Our findings provide the first evidence of how coffee impacts short-term taste sensitivity and consequently the way we sense and perceive food following coffee intake—an important insight in the context of gastronomy, as well as in chemosensory testing procedures.